What do Peruvian Children understand and Say in Early Childhood? Preliminary Results on Vocabulary Size and Composition between 8 and 30 Months of Age - Fernández-Flecha, María (2021)
We analyzed the size and composition of the receptive and productive vocabulary of Spanish-speaking Peruvian children in two age groups: 8 to 15 and 16 to 30 months. We look for significant changes in size based on the age and gender of the children. Regarding the composition of the vocabulary, we consider only those items that occupy the first 50 positions as long as they are understood or produced by at least 50% of the children, and we analyze them on the basis of an exhaustive list of grammatical categories and the children´s age. Finally, we explore the existence of correlations between certain grammatical categories whose syntactic relations could suggest a parallel development, and we compare our results with those of similar studies.